Individual and community-level determinants and spatial distribution of prenatal HIV test uptake in Ethiopia: Spatial and multilevel analysis - Tsega, Nuhamin Tesfa; Belay, Daniel Gashaneh; Asratie, Melaku Hunie; Gashaw, Moges; Endalew, Mastewal; Aragaw, Fantu Mamo (Frontiers in Public Health, 2023)
Introduction: Although the prevalence of HIV infection is high among women, evidence suggests the uptake of HIV testing during prenatal services in Ethiopia is scarce. Therefore, the aim of this study was to investigate individual and community level determinants and spatial distribution of prenatal HIV test uptake in Ethiopia based on the 2016 EDHS. Methods: Data were accessed from the 2016 Ethiopian Demographic and Health Survey. The Bernoulli model was fitted using SaTScan V.9.6 to identify cold spot areas and ArcGIS V.10.7 to explore the spatial distribution of prenatal HIV test uptake. Stata version 14 software was used to extract, clean, and analyze the data. A multilevel logistic regression model was used to identify the individual and community-level determinants of prenatal HIV test uptake. An adjusted odds ratio with a corresponding 95% confidence interval (CI) was used to declare significant determinants of prenatal HIV test uptake. Results: The prevalence of HIV test uptake was 34.66% (95% CI: 33.23, 36.13%). The spatial analysis revealed that the distribution of prenatal HIV test uptake was significantly varied across the country. In the multilevel analysis, those women who attained primary education (AOR = 1.47, 95%CI: 1.15, 1.87), and secondary and higher education (AOR = 2.03, 95%CI: 1.32, 3.11), women from middle (AOR = 1.46; 95%CI: 1.11, 1.91) and rich household wealth status (AOR = 1.81; 95%CI: 1.36, 2.41), having health facilities visits in the last 12 months (AOR = 2.17; 95%CI: 1.77, 2.66), women who had higher (AOR = 2,07; 95%CI: 1.66, 2.59) and comprehensive HIV related knowledge (AOR = 2.90; 95%CI: 2.09, 4.04), who had moderate (AOR = 1.61; 95%CI: 1.27, 2.04), lower (AOR = 1.52; 95%CI: 1.15, 1.99), and no stigma attitudes (AOR = 2.67; 95%CI: 1.43, 4.99), and living in large central (AOR = 0.37; 95%CI: 0.15, 0.91), and small peripherals areas (AOR = 0.22; 95%CI: 0.08, 0.60) were significantly associated with prenatal HIV test uptake. Conclusions: In Ethiopia, prenatal HIV test uptake had significant spatial variations across the country. Both individual and community level determinants were found to be associated with prenatal HIV test uptake in Ethiopia.